Depletion of florfenicol and florfenicol amine in eggs of laying hens and growing pullets after oral administration. Issue 9 (1st September 2020) - Li, Xia; Chen, Lu; Yue, Hui; Feng, Hua; Xu, Enmin; Wei, Xiuli; Han, Xiaoli; Deng, Ligang; Li, Zengmei
ABSTRACT: In this study, we carried out two experiments to evaluate depletion of florfenicol (FF) and its metabolite florfenicol amine (FFA) in eggs from growing pullets and laying hens. Eggs were collected, and the egg white and yolk were separated. FF and FFA were analysed by liquid chromatography-tandem mass spectrometry. In the first experiment, 30 laying hens were given FF capsules at 50 mg/kg·bw −1 daily for 5 d. FF + FFA was detectable in egg white (1, 190 µg/kg) on day 1 of treatment and increased slowly thereafter. After treatment, the residues decreased rapidly and were not detected by day 11. In yolk, residues were detected at a lower concentration on day 1 and increased dramatically to 3308 µg/kg at the end of treatment. The residues remained steady over the next 4 days post-treatment, followed by a rapid drop. Residues were not detectable on day 15 post-treatment. In the second experiment, four groups (B1 through B4) of growing pullets were treated in the same manner for 25, 20, 15, and 10 days before egg primiparity. FF and FFA were not detectable in the eggs of group B1; however, they were detectable in egg whites and yolks of groups B2, B3, and B4. The highest total concentrations of FF and FFA detected in egg white and yolk of group B4 were 3, 190 µg/kg and 3, 214 µg/kg, respectively. Thereafter, concentrations decreased until no more residues were detected in egg whites or yolks on days 17 and 21 post-treatment, respectively. Therefore, drug treatment should be stopped at least 21 d before primiparity of growing pullets to guarantee food safety.